The basis and strategies of gender mainstreaming in Islamic education: A conceptual review - Muhamad Agus Mushodiq; Muhammad Kasih Majeed Chaudhary (Indonesian Journal of Educational Management and Leadership, 2025)
ABSTRACT Purpose − This paper seeks to articulate the foundations and strategies for gender mainstreaming within Islamic education. This topic is urgent, as gender inequality in education continues to be a significant issue today. Furthermore, Islam is frequently viewed as contradictory to the principle of gender equality due to its textual interpretations of the Quran and hadith, which serve as primary sources for Muslims. Method − The researchers conducted a qualitative literature review of various texts related to Islamic education, aiming to gather insights from Muslim philosophers regarding the foundations of gender mainstreaming in education. Data collection involved techniques such as active listening and note-taking. The analysis of the data was carried out in three phases: reduction, presentation, and inductive conclusion Findings − Based on the analysis conducted, it is clear that Islam actively supports gender mainstreaming efforts in education to foster social justice and equality. Islam does not differentiate between men and women in terms of their opportunities to acquire knowledge and become exemplary individuals, or khalifatullah fi al-ardh (stewards of the earth). Muslim philosophers endorse gender equality in education both implicitly and explicitly, with no philosophers advocating for discrimination against either gender in the pursuit of quality education. To effectively implement gender mainstreaming in Islamic education, the following strategies should be adopted: (1) Emphasize the importance of allowing students the freedom to choose their fields of study. (2) Foster collaboration between the state and society—through influential organizations or figures—to advance gender mainstreaming in education. (3) Establish a school environment that is rooted in principles of gender equality. (4) Develop educational practices and school management that are sensitive and responsive to gender considerations. (5) Encourage the government, particularly the Ministry of Religious Affairs, to create model or pilot schools that exemplify gender equality and can serve as examples for replication. (6) Provide intensive training and seminars focused on gender issues for educators within both the Ministry of Education and the Ministry of Religious Affairs.